EVALUASI KUALITAS BERAS VARIETAS PARE WANGI PADA BERBAGAI TINGKAT KELEMBABAN DAN SALINITAS TANAH - Arsa, I Gusti Bagus Adwita; Lalel, H.J.D. (CROP AGRO, Scientific Journal of Agronomy, 2023)
The purpose of this research was to determine aroma quality of rice and nutritional contents of upland rice of Pare Wangi variety under various levels of soil moisture and salinity, and determine correlation between the aroma quality and the nutritional content of rice. The research was started with planting seeds of Pare Wangi variety in the pot experiment. Experiment was conducted using Completely Randomized Design (CRD) that was arranged factorially by three replications. The samples of harvested grain then were taken to the laboratory to be tested for the aroma quality and other qualities of the rice. The aroma quality was determined on the basis of the aroma score of organoleptic-test results and 2-AP content of the rice, while other rice qualities include: percentage of white rice and head rice, rice water content, content of ash, fat, carbohydrate, protein, starch, amylose, and amylopectin. Data were analyzed by analysis of variance, HSD of 5% significantly level, and descriptive. Then, to find out the relationship between aroma quality and nutritional contents were carried out simple correlation analysis. The results showed that the decrease in soil moisture level caused a decrease in the quality of milled grain and the nutritional contents of rice, but did not show a significant decrease in the protein and carbohydrate content of rice. Soil moisture at 75% FC level caused the best 2AP content of rice and aroma score. The increase in salinity with the addition of NaCl salt up to 4 g NaCl kg-1 soil caused a decrease the quality of milled grain, content of ash, fat and protein. Salinity level of 1 and 2 g NaCl kg-1 soil gave the highest 2AP content of rice, but the effect was not significant on the rice aroma score. Both 2AP content and aroma score of rice were not significantly correlated with all nutritional contents of rice analyzed.